Theory Meets Empiry: A Citation Network Analysis. (22nd August 2018) - Fitzpatrick, Courtney L; Hobson, Elizabeth A; Mendelson, Tamra C; Rodríguez, Rafael L; Safran, Rebecca J; Scordato, Elizabeth S C; Servedio, Maria R; Stern, Caitlin A; Symes, Laurel B; Kopp, Michael
Abstract: According to a recent survey, ecologists and evolutionary biologists feel that theoretical and empirical research should coexist in a tight feedback loop but believe that the two domains actually interact very little. We evaluate this perception using a citation network analysis for two data sets, representing the literature on sexual selection and speciation. Overall, 54%–60% of citations come from a paper's own category, whereas 17%–23% are citations across categories. These cross-citations tend to focus on highly cited papers, and we observe a positive correlation between the numbers of citations a study receives within and across categories. We find evidence that reviews can function as integrators between the two literatures, argue that theoretical models are analogous to specific empirical study systems, and complement our analyses by studying a cocitation network. We conclude that theoretical and empirical research are more tightly connected than generally thought but that avenues exist to further increase this integration.